Changes in the generic diversity of brachiopods at the intervals of the largest Phanerozoic mass extinctions - D. A. Ruban (Известия высших учебных заведений: Геология и разведка, 2025)
Background. Brachiopods evolved throughout the Phanerozoic, and their study contributes to the knowledge of the largest biotic crises. Accumulation and revision of paleontological information require regular re-evaluation of the influence of these crises on the taxonomic diversity of the given group of marine organisms.Aim. To study the dynamics of the generic diversity of brachiopods under the influence of the most famous mass extinctions of the Phanerozoic based on three datasets representing different “generations” of paleontological compilations.Materials and methods. On the basis of each dataset, a curve of generic diversity of brachiopods is constructed. Three curves are drawn against the uniform geological time scale. For the periods of mass extinctions considered, a decrease in the number of genera and relations to the preceding and forthcoming trends of diversity changes are estimated.Results. The constructed curves indicate that the end-Ordovician, Permian/Triassic, Triassic/Jurassic, and Cretaceous/Paleogene mass extinctions triggered a decrease in the generic diversity of brachiopods. The largest was the influence of the Permian/Triassic catastrophe. Conversely, the effect of the Frasnian–Famennian (Late Devonian) event was either minimal or absent. The trends of diversity changes before and after critical intervals showed a different dynamic.Discussion. The retrospective analysis of the curves of brachiopod generic diversity showed that newer information may have indicated a higher or lower intensity of crises in different cases. Moreover, the changes of the “generations” of paleontological compilations did not contribute to an improved understanding of the dynamics of the considered genera. Therefore, the three curves should be used in combination, treating the difference between them as the degree of error.Conclusion. The results obtained indicate the vulnerability of brachiopods to mass extinctions, although to a different extent. Moreover, some estimates remain uncertain, which substantiates further research into of the development of brachiopods during the critical intervals of the geological history.